2022
DOI: 10.3390/cells11213438
|View full text |Cite
|
Sign up to set email alerts
|

The Ion Channel Gene KCNAB2 Is Associated with Poor Prognosis and Loss of Immune Infiltration in Lung Adenocarcinoma

Abstract: The malignancy with the greatest global mortality rate is lung cancer. Lung adenocarcinoma (LUAD) is the most common subtype. The evidence demonstrated that voltage-gated potassium channel subunit beta-2 (KCNAB2) significantly participated in the initiation of colorectal cancer and its progression. However, the biological function of KCNAB2 in LUAD and its effect on the tumor immune microenvironment are still unknown. In this study, we found that the expression of KCNAB2 in tissues of patients with LUAD was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…MIP-1α, MIP-1β and MIP-2, as important chemokines, play pivotal role in attracting immune cells to tumor tissues sites [ 22 , 23 ]. However, other studies also found that higher expression of MIP-1α, MIP-1β or MIP-2 were also associated with poorer prognosis and decreased survival rate in lung adenocarcinoma patients [ [24] , [25] , [26] ]. High levels of MIP-1α have also been linked to promoting cancer cells growth and survival by stimulating tumor neovascularization [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…MIP-1α, MIP-1β and MIP-2, as important chemokines, play pivotal role in attracting immune cells to tumor tissues sites [ 22 , 23 ]. However, other studies also found that higher expression of MIP-1α, MIP-1β or MIP-2 were also associated with poorer prognosis and decreased survival rate in lung adenocarcinoma patients [ [24] , [25] , [26] ]. High levels of MIP-1α have also been linked to promoting cancer cells growth and survival by stimulating tumor neovascularization [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…KCNAB2 mRNA and protein expression is significantly downregulated in immortalized NSCLC cell lines as well as in local NSCLC tissues when compared with human alveolar epithelial cells and corresponding adjacent normal tissues. Lyu et al, have shown that KCNAB2 expression is downregulated in lung adenocarcinoma [ 22 ]. The proliferation and migration ability of lung cancer cells was altered after KCNAB2 overexpression by plasmid transfection, although the difference is not statistically significant [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lyu et al, have shown that KCNAB2 expression is downregulated in lung adenocarcinoma [ 22 ]. The proliferation and migration ability of lung cancer cells was altered after KCNAB2 overexpression by plasmid transfection, although the difference is not statistically significant [ 22 ]. However, in this study we confirmed that in different NSCLC cells, ectopic overexpression of KCNAB2 potently inhibited the cell malignant biological behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kv subfamily A regulatory beta subunit 2 (KCNAB2) participates in neuroendocrine functions as well as in certain cancer processes [105]. Its low expression in LUAD is associated with accelerated tumor growth and poor prognosis, whereas its overexpression contributes to the expression of chemokines required for immune cell migration [104].…”
Section: Voltage-gated Potassium Channelsmentioning
confidence: 99%